PRESENT STATUS OF WORKERS IN READY-MADE GARMENTS INDUSTRIES IN BANGLADESH - Farhana, Kaniz; Syduzzaman, Md.; Munir, Md. Shayekh (European Scientific Journal, ESJ, 2015)
The Ready Made Garment (RMG) industry has been placed the largest export earnings of Bangladesh where more than 5000 garment factories are running, employing over 4 million people of which more than 80% workers are women. RMG industry is considered as the back bone of the country’s economy-The main strength of RMG sector in Bangladesh is poorly paid garment workers. This article depicts the wages level, age group, gender, family life and working hours of workers in RMG industries in Bangladesh. It is notable that the living situation of garments workers may change last couple of years. Nowadays their children also go to school & they can serve their old parents. Already government fixed the minimum wages for their better standard of living. Though it is not sufficient but it is improving.